Prototipe Monitoring Daya Listrik dan Pengendalian Perangkat Elektronik Skala Industri Berbasis IoT di CV. Wellracom Nusantara Surabaya - Samsul Huda; Trio Bekti Imansah; Elvianto Dwi Hartono (Fakultas Teknologi Informasi Universitas Merdeka Pasuruan, 2021)
The electricity bill accounts for a considerable amount of the full operating costs of industries. CV. Wellracom Nusantara has a lot of electronic equipment and industrial machines for production. Here, the company does not really know the electricity usage each month. They only know the significant amount of bill payments and over-budget when the electricity bill comes. Therefore, it is crucial for companies to accurately estimate future electricity costs as a strategy to reduce over-budget and uncontrolled costs. To overcome the problems, we propose a prototype monitoring system to make it more comfortable to monitor the use of electrical power in the company. This solution allows the electricity consumption from all devices to be monitored and controlled. The prototype monitors the use of electrical energy from each device and controls the electronic devices. The proposed solution adopts IoT technology using industrial-scale devices. This can monitor electricity consumption data from each device in real-time, record historical data from daily to monthly, send notifications, and control on/off devices. This prototype has an accuracy of 98% of the reading measurement results compared to the digital AVOmeter. Through a simple experiment using electric power loads of two light bulbs and two laptop chargers for 24 hours, we confirmed that the implemented prototype runs correctly.Keywords— electricity usage management, electricity bill, IIoT, IoT